Management of Educational Curriculum Integration in the Implementation of Full Day School at SDIT Nurul Islam Semarang - Dona Muhammad Syukur; Fakhruddin; Suwito Eko Pramono (Universitas Negeri Semarang, 2026)
This study aims to describe and analyze the planning, organizing, implementation, and evaluation of the curriculum within the Full Day School system at SDIT Nurul Islam, Tengaran District, Semarang Regency. As an integrated Islamic educational institution, this school faces challenges in synchronizing the national curriculum with the specific boarding school (pesantren) or religious curriculum without causing student burnout. The research method employed is descriptive qualitative. Data were collected through participatory observation, in-depth interviews with the principal, teachers, and management staff, as well as documentation studies related to learning tools. The results indicate that the management of Full Day School implementation at SDIT Nurul Islam Tengaran is carried out through holistic curriculum integration, where cognitive, affective, and psychomotor aspects are developed through extended learning hours. The key to successful implementation lies in varied scheduling management, the use of active learning methods, and the strengthening of character education through daily religious habituation. Obstacles identified include limited infrastructure to support student rest and the need for improved pedagogical competence among teachers in managing long-duration classes. This study concludes that structured and collaborative management between the school and parents is a determining factor in the effectiveness of the Full Day School system in achieving educational quality targets at SDIT Nurul Islam Tengaran.